Modern weddings in Uzbekistan: ritual change from 'above' and from 'below'. Issue 1 (2nd January 2016) - Trevisani, Tommaso
Abstract : Under the new conditions of independence, wedding ceremonies in Uzbekistan have increasingly diversified along growing social and economic divides. Recent state measures to curb ritual expenditures follow the furrow of a long tradition of criticism against ritual prodigality which, however, falls short of its self-set target of enforcing more 'rational' rituals. Based on fieldwork conducted in the Ferghana Valley, this paper sheds a new light on the controversy around 'excessive ritual expenditures' by discussing tensions in local practices arising from changing livelihoods and consumption patterns, on the one hand, and, on the other, from an ambivalent state policy that aims at containing ritual expenditures and social polarization, while also promoting an ideal of modern wedding that undermines the very aim of the policy.